THE RELATIONSHIP BETWEEN PRESERVICE ENGLISH TEACHERS’ PERCEPTION OF WATCHING ENGLISH VIDEO ON YOUTUBE AS A HABIT AND LISTENING SKILL ACHIEVEMENT - Nur Anggi Irana; Rita Hayati; Dedi Kurniawan (The Journal of English Literacy Education: The Teaching and Learning of English as a Foreign Language, 2021)
Watching English videos on YouTube is one of the alternatives in order to improve students’ listening comprehension. The aim of this study is to discover whether or not there is a significant correlation between the perception of habit of watching English videos on YouTube and listening skill achievement. The participants of the study were 51 students of English Education Study Program in Palembang. There were two instruments used: (1) The Habit of Watching English Videos on YouTube Questionnaire, and (2) listening mastery score from listening course they took. The data were then analysed using Pearson Product Moment in SPSS 25. The results show that there is no significant correlation between the habit of watching English videos on YouTube and listening mastery of the students, r(49) = - .26, p < .01. This study also provided discussions and recommendations for future research.